Human Umbilical Cord Mesenchymal Stem Cells Therapy for Insulin Resistance: A Novel Strategy in Clinical Implication - Bi, Sheng; Nie, Qing; Wang, Wei-qun; Zhu, Yan-li; Ma, Xue-mei; Wang, Chun-min; Zhang, Bao-cheng; Li, Han-yang; Zhang, Qiang; Chen, Guang (Current Stem Cell Research & Therapy, 2018)
There is increasing evidence reporting that as a common phenomenon in MetS relative diseases, insulin resistance (IR) is regarded as an independent etiological factor and a warning indicator of MetS occurrence. Therefore, for the special group (overweight or obesity), clinical regular monitoring of IR is an important basis for the prevention and early intervention of MetS relative diseases. This surveys reveals that human umbilical cord mesenchymal stem cells (HUC-MSCs)possess a kind of potential: it may become a possible theraphy for IR in type 2 diabetes mellitus (T2DM) and related diseases. Specific emphasis is focused on evaluating the improvement IR function of HUC-MSCs under the background of development in vitro and in vivo. Next, the action mechanisms of HUC-MSCs is discussed, and some of their advantages and disadvantages in the course of clinic application are presented. The final section highlights the application of HUC-MSCs in T2DM and relative diseases at this stage. Up to now, although many questions remain unresolved, we still consider that HUC-MSCs is one of the best therapy ameliorating IR in the future.
Keywords: Human umlilical cord mesenchymal stem cells